Maximum Principles for Fourth Order Uniformly Elliptic Equations with Applications, “This paper has been withdrawn” - Dhaigude, D. B.; Dhaigude, R. M.; Lomte, Gajanan (International Journal of Applied Mathematical Research, 2012)
This paper has been withdrawn.